Ingredients and change processes in occupational therapy for children: a grounded theory study. (4th May 2017) - Armitage, Samantha; Swallow, Veronica; Kolehmainen, Niina
Abstract: Background: There is limited evidence about the effectiveness of occupational therapy interventions for participation outcomes in children with coordination difficulties. Developing theory about the interventions, i.e. their ingredients and change processes, is the first step to advance the evidence base. Aim: To develop theory about the key ingredients of occupational therapy interventions for children with coordination difficulties and the processes through which change in participation might happen. Material and methods: Grounded theory methodology, as described by Kathy Charmaz, was used to develop the theory. Children and parents participated in semi-structured interviews to share their experiences of occupational therapy and processes of change. Data collection and analysis were completed concurrently using constant comparison methods. Results: Five key ingredients of interventions were described: performing activities and tasks; achieving; carer support; helping and supporting the child; and labelling. Ingredients related to participation by changing children's mastery experience, increasing capability beliefs and sense of control. Parents' knowledge, skills, positive emotions, sense of empowerment and capability beliefs also related to children's participation. Conclusion and significance: The results identify intervention ingredients and change pathways within occupational therapy to increase participation. It is unclear how explicitly and often therapists consider and make use of these ingredients and pathway.